On Characteristic Polynomial of Antiadjacency Matrix of A Line Digraph - Muhammad Irfan Arsyad Prayitno; Kiki Ariyanti Sugeng (Jurusan Matematika FMIPA Universitas Andalas Padang, 2022)
In this paper, we find the characteristic polynomial of the antiadjacency matrix of a line digraph. There are recent studies on the relation between the characteristic polynomial of the adjacency matrix and its line digraph, we are also interested in finding the connection between the antiadjacency matrix of a digraph and its line digraph. In this paper, we show the connection of characteristic polynomial of the antiadjacency matrix between an acyclic digraph and its line digraph.